NILAI NILAI ISLAM MODERAT PERSPEKTIF KH ALI MAKSUM KRAPYAK DAN RELEVANSINYA DENGAN PENDIDIKAN AGAMA ISLAM - Moch Holilulloh; Muhammad shohib (JOURNAL SAINS STUDENT RESEARCH, 2025)
Universitas Kiai Abdullah Faqih Gresik Abstrak Indonesia is a diverse country, consisting of various ethnicities, religions, and cultures, as reflected in the motto "Unity in Diversity." However, the reality of pluralism is often disrupted by conflicts with religious undertones, hate speech, and acts of intolerance. Religious radicalism arises from an extreme understanding of sacred texts without considering the goals of Sharia.In this context, Wasathiyyah Islam or moderate Islam becomes important. Based on the thoughts of K.H. Ali Maksum in the book Hujjah Ahlus Sunnah Wal Jama’ah, there are four main values that form the foundation of moderate Islam:At-Tawasuth (the middle attitude),Tasamuh (tolerance),Tawazun (balance),Amar Ma’ruf Nahi Munkar (encouraging good and preventing wrongdoing).This research uses library research methods and finds that the book teaches the importance of respecting differences, rejecting violence, and promoting a critical and democratic attitude. These values are essential to be integrated into education.